Konsep Dasar Psikologi Pendidikan: Basic Concepts of Educational Psychology - Arlesya Kurniansi (Litera Academica Publishing, 2025)
Educational psychology is an essential foundation for understanding how learners think, feel, and behave throughout the learning process. This study emphasizes that the role of educational psychology extends beyond explaining learning theories; it also involves applying psychological principles to create effective, inclusive, and humanistic learning experiences. In the context of Indonesian education—which faces challenges such as diverse learner characteristics, social disparities, and rapid technological development—understanding educational psychology has become an urgent necessity for educators. By integrating behavioristic, cognitive, humanistic, and constructivist theories, educators can design holistic and evidence-based learning strategies. This study asserts that mastering the fundamental concepts of educational psychology is not only an academic requirement but also a moral responsibility in shaping an education system oriented toward the intellectual, emotional, and spiritual development of learners.